Obesity, Comorbidities, and the Associated Risk among Patients Who Underwent Total Knee Arthroplasty in Alberta - Baghbani-Naghadehi, Fatemeh; Armijo-Olivo, Susan; Prado, Carla M.; Woodhouse, Linda J. (The Journal of Knee Surgery, 2022)
Obesity, a common risk factor for osteoarthritis (OA), accelerates joint deterioration resulting in the need for early total knee arthroplasty (TKA). The role of obesity in the management of OA remains a controversial topic. In this study, we examined whether obesity along with other comorbidities is associated with peri/postoperative complications in patients who underwent primary unilateral TKA in Alberta, Canada. A retrospective secondary analysis was performed on data extracted from data repository of patients (n = 15,151) who underwent TKA between 2012 and 2016. The sample was divided into five groups based on body mass index (BMI) classification developed by the World Health Organization. The associations between dependent variable (presence or absence of a complication or comorbidity) with the independent variables (year of surgery, age, sex, length of surgery, and BMI groups) were examined using binomial logistic regression. Results showed that obese classes I, II, and III, irrespective of other covariates, were more likely to have diabetes and pulmonary embolism (p < 0.001) compared with the normal BMI group. Patients with obese class III compared with the patients in normal BMI group were more likely to have deep wound infection (p = 0.04). Patients with comorbidities were more likely to have a blood transfusion, infection, pulmonary embolism, and readmission. Patients in higher BMI groups or with comorbidities were more likely to experience peri/postoperative complications following TKA, though the level of risk depends on the severity of obesity. These findings may be used by health care providers to educate patients in higher BMI groups about the risks of TKA and optimize comorbidities prior to the surgery.
Keywords: obesity; total knee arthroplasty; osteoarthritis; comorbidities; complications